Pemberdayaan Masyarakat melalui Perubahan Mindset Masyarakat Humbahas Menuju Tercapainya Ekowisata - Hamdi Hamdi; Sukardi Sukardi; Nana Dyki Dirbawanto (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Humbang Hasundutan Regency (Humbahas) is one of the areas in the province of North Sumatra which has a very large agricultural land. Changes in land use have given rise to a variety of new problems. Whereas agricultural development can be done through; intensification, extensification, diversification and rehabilitation in an integrated manner to increase farmers' income. If ecotourism is the management of nature and community culture that ensures sustainability and welfare, while conservation is an effort to maintain the continuity of the use of natural resources for the present and the future. Ecotourism will be an alternative system for the community to increase the potential of the land in their area. The purpose of holding this service activity is to change the mindset of the public humbahas about how to optimize land use so as to avoid polemics over land grabs. The method used to achieve this goal is to carry out several stages including surveys, socialization, procurement of tools and goods, technical training and assistance. The results of this service activity have changed the mindset of the Humbahas community for the better as evidenced by the maximum optimization of land.